A Budget Impact Analysis of Gene Therapy for Sickle Cell Disease: The Medicaid Perspective. Issue 12 (December 2021) - DeMartino, Patrick; Haag, Meredith B.; Hersh, Alyssa R.; Caughey, Aaron B.; Roth, Joshua A.
Abstract : (Abstracted from JAMA Pediatr 2021;175(6):617–623) Sickle cell disease (SCD) affects approximately 100, 000 people in the United States, with a promising gene therapy option for treatment likely to enter the market soon. However, this therapy is expected to cost over 1 million.